(untitled) (Prosiding Keislaman dan Sains, 2025)
Murabahah binds the sale and purchase of collateral objects at the time of the financing contract, not using collateral that has been previously sold and is fictitious. This research aims to straighten out the procedural check on the spot and the recross check of collateral from the analyst and decision-maker before deciding on financing approval. Data analysis and measurement in this research uses a qualitative approach with a descriptive explanation level. Based on the place, this research includes field research. Based on the type and strategy of research findings, this research is a case study. The results of this study describe and illustrate the Standard Operational Procedure (SOP) that should be used in checking collateral objects in Murabahah financing types, which are usually additional collateral for prospective customers. The analyst team from maker, checker, and approval in Murabahah financing must carry out checks on the spot and recross checks consistently and objectively on the collateral of prospective customers. In other words, not just looking at the report. Collateral object deviations often occur in the field due to the pursuit of financing targets. Although collateral is an additional guarantee, it has an important role in determining the fulfillment of the collateral assessment ratio. The conclusion of this research is that it is very important to coordinate at every level solidly to double-check the collateral repeatedly to avoid errors in the Murabahah financing determination procedure.